A study to determine the short term outcome of traction treatment for femoral shaft fractures in children aged 6-13 years at university teaching hospital (UTH) from 2007-2009 - Kabambi, Harrison (Lusaka: University of Zambia , School of Medicine, 2010)
The study sought to determine the short term outcome of traction treatment for femoral shaft fractures in children 6-13 years at UTH.Femoral shfts have varying outcomes worldwide depending on the methods used, and this is dependent upon age and weight of a patient, location, character of fracture and associated injuries.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Femur fractures